2007
DOI: 10.1634/stemcells.2006-0701
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin Enhances Generation of CD34+ Cells from Human Embryonic Stem Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Prior studies have demonstrated that addition of TPO increases formation of primitive hematopoietic progenitors in primate EB differentiation models [39]. It was also shown that TPO and VEGF induce early hematopoietic differentiation of EB-derived human ES cells [40]. Our data show that inclusion of both VEGF and TPO in the medium enhances hematopoietic differentiation, as evidenced not only by up-regulated expression of CD34 and SCL, but also by increased numbers of CFCs at day 14.…”
Section: Discussionsupporting
confidence: 69%
“…Prior studies have demonstrated that addition of TPO increases formation of primitive hematopoietic progenitors in primate EB differentiation models [39]. It was also shown that TPO and VEGF induce early hematopoietic differentiation of EB-derived human ES cells [40]. Our data show that inclusion of both VEGF and TPO in the medium enhances hematopoietic differentiation, as evidenced not only by up-regulated expression of CD34 and SCL, but also by increased numbers of CFCs at day 14.…”
Section: Discussionsupporting
confidence: 69%
“…Because it is well known that signaling mediated by the TPO/c-Mpl axis is indispensable for megakaryopoiesis, 24,25 we suggest that augmented expression of c-Mpl mediated via a VEGF signaling pathway increases megakaryopoiesis and thrombopoiesis to levels not seen in the absence of VEGF ( Figure 3A,B), which is consistent with a recent report. 26 Because the cells making up ES-sacs manifest characteristics similar to those of endothelial cells (Figure 2A,B), and because bFGF and PlGF, like VEGF, are necessary for endothelial cell growth, [27][28][29] we next assessed the respective capacities of bFGF or PlGF to promote the generation of ES-sacs and hematopoietic progenitors. Interestingly, bFGF at concentrations of 2.5 or 10 ng/mL exerted a dose-dependent inhibitory effect, while PlGF at 50 ng/mL tended to increase the generation of ES-sacs ( Figure 3C) and platelets (data not shown).…”
Section: Org Frommentioning
confidence: 99%
“…In a series of manuscripts Bhatia's group has established serum-based cultivation conditions with mesoderm/hematopoietic cell-inducing cytokines (BMP-4, VEGF 165 , IL-3, IL-6, SCF, FLT-3L, and G-CSF) that lead to a high of blood cells in culture [144][145][146][147][148][149]. Similarly, we have shown that TPO and VEGF induce generation of CD34+ cells form human ES cells [150]. Other groups have also studied the expansion of lympho-myeloid hematopoietic tissue from hES cells via different culture methodologies [148; 149; 151-154].…”
Section: Recent Progress With Human Es Cells (Hes): Blood From Human mentioning
confidence: 83%